New millennium Annulus Engine Mechanism / Azmi Ab. Rahman, Hairulanam Mat Swadi and Halek Halimoon - Ab. Rahman, Azmi; Mat Swadi, Hairulanam; Halimoon, Halek (Faculty of Mechanical Engineering, 2003)
Nowadays, the mechanical automotive engineering technologies are advancing in a greater pace towards the most advanced automobile system of combustion with the maximum elimination of mechanical loss. The main scope of this thesis is to present the basic concept of how the New Annulus Engine Machine operates and its advantages. In conjunction with this fact, we also distinguished the features it offers with the current engine design so it would have concrete points to compete with them. New Annulus Engine Machine still implies the same concept as a 4-stroke engine i.e. intake, compress, power, and exhaust except that it operates neither in line nor V-shape but in the same circular plane as do a scissor. Here, we include the construction of the engine; diagrams on how it operates and several remedies it offers to the common troubleshoot of present automobile engine. Typical specifications and dimensions are also included. During the planning and preparation of this thesis, we would like to thank once more to all the supportive individual involved in completing this thesis especially Dr. Rahim Atan for his kind assistances. Critics and comments are most welcomed by us. We need adequate motivation support in order to bring this thesis to a higher standard.